RANCANG BANGUN SISTEM PEMANTAUAN DAN PENGENDALIAN BEBAN LISTRIK BERBASIS INTERNET OF THINGS (IoT) - Erwan Eko Prasetiyo; Farid Ma’ruf (IST AKPRIND Yogyakarta, 2018)
One of the human needs today is electricity. Almost all human activities everyday can not be separated from the use of electricity. However, the basic electricity tariff is now increasing. Efforts to save electricity are needed to reduce waste of electricity costs. One way to save electricity proposed in this research is load monitoring and control system based Internet of Things (IoT). This research aims to design, implement and know the performance of monitoring system and load control based on Internet of Things (IoT). Tools used in the design of this system include: NodeMCU Microcontroller ESP8266, Relay Driver, LED indicator, Current sensor. Research stages include literature study, problem and goal formulation, data collection, media design, implementation, result analysis, conclusion and report writing. Analysis of the results of research conducted by performing system performance test functionality of each part and performance test system as a whole. The results showed that the design of monitoring system and load control based on Internet of Things (IoT) is divided into 3 (three) main parts namely input, process and output. The input section consists of ACS712 current sensors as an electric load current detector. The process part consists of an integrated microcontroller in the NodeMCU ESP8266 device. The output section consists of 4-channel relays as circuit breakers and electrical load connectors. Implementation of the system is designed in two parts, namely hardware and software. Hardware consists of nodeMCU 12E microcontroller and ACS712 sensor while the software consists of Arduino IDE as its compiler and Cayenne as Internet of Thigs (IoT) service. System performance with 4 load points can work well according to plan. Power monitoring and control system can be done through computer or smartphone device. All sensors and displays can function properly but the speed still depends on the speed of internet connection.